2012
DOI: 10.1159/000335781
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Aortic Valve Implantation in Dialysis Patients

Abstract: Background/Aims: Transcatheter aortic valve implantation (TAVI) has emerged as a new therapeutic option for high-risk patients. However, dialysis patients were excluded from all previous studies. The aim of this study is to compare the outcomes of TAVI for dialysis patients with those for patients with chronic kidney disease (CKD) stages 3 and 4 and to compare TAVI with open surgery in dialysis patients. Methods: Part I: comparison of 10 patients on chronic hemodialysis with 116 patients with non-dialysis-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 33 publications
4
12
0
Order By: Relevance
“…In the present study, advanced CKD was associated with worse outcomes (mortality, bleeding, and stroke) in high‐risk TAVR patients. This is in line with previous studies demonstrating that advanced CKD is an independent risk factor for mortality, stroke, and bleeding events in TAVR patients . The findings herein corroborate these earlier reports and the observation that mortality, bleeding events, and stroke cluster in this cohort.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, advanced CKD was associated with worse outcomes (mortality, bleeding, and stroke) in high‐risk TAVR patients. This is in line with previous studies demonstrating that advanced CKD is an independent risk factor for mortality, stroke, and bleeding events in TAVR patients . The findings herein corroborate these earlier reports and the observation that mortality, bleeding events, and stroke cluster in this cohort.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, 6‐month survivability was 74.4%. This was similar to Rau et al who reported 6‐month survival rates of TAVR in 10 high‐risk chronic hemodialysis patients to be 80%. A collaborative report from four European centers reported outcomes of 33 patients on hemodialysis after TAVR with a 1‐year survival rate of only 54.8% .…”
Section: Discussionsupporting
confidence: 90%
“…It is interesting to note that TAVR does not increase mortality in patients with ESRD and is therefore an attractive option in the dialysis patient . One can argue that in subjects with ESRD, where all the functions of the kidney are met by renal replacement therapy (RRT), contrast‐mediated and athero‐embolic effects have minimal adverse impact.…”
Section: Pathogenesis and Risk Factorsmentioning
confidence: 99%